Importing Air Pollution? Evidence from China's Plastic Waste Imports - Kerstin Unfried; Feicheng Wang (Institute of Labor Economics (IZA), 2022)
Plastic waste trade has grown considerably in the last decades and has caused severe environmental problems in recipient countries. As the largest recipient, China has permanently banned the imports of plastic waste since 2018. This paper examines the causal effect of plastic waste imports on air pollution by exploiting China's experience of importing plastic waste and the recent import ban. Combining data on plastic waste imports with PM2.5 data at the city level for the years 2000-2011, we find that plastic waste imports increased PM2.5 density significantly. This effect is linked to expanded production in the waste processing sector and an increased number of incineration. To evaluate the impact of the import ban on air quality, we employ daily data on air pollution between 2015 and 2020. Our difference-in-differences results show that affected cities, relative to other cities, experienced a significant improvement in air quality following the ban. These findings suggest potential environmental gains from banning plastic waste imports in other countries.
Keywords: F18; F64; Q53; Q56; 330; PM2.5; air pollution; waste import ban; plastic waste trade; China